2016
DOI: 10.1016/j.psychsport.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding overuse injuries in rhythmic gymnastics: A 12-month ethnographic study

Abstract: Objectives: This study aimed to gain an in-depth understanding of overuse injuries in rhythmic gymnastics from a psychosocial perspective. More specifically, it examined how sport culture impacts overuse injuries. Design: To develop an understanding of the culture of rhythmic gymnastics and gymnasts' behaviour within the context of this culture, ethnography was the chosen method and written product of this research. Method: A 12-month ethnography was conducted in an elite rhythmic gymnastics club in Italy, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 39 publications
3
63
0
1
Order By: Relevance
“…This lack of open communication between athletes and coaches, together 1 with pain normalisation and impression management behaviours, was shown to influence the 2 development of overuse injuries. Overall, the gymnasts adhered to the cultural values and 3 norms inherent within the gymnastics environment by displaying appropriate behaviours 4 reinforced by the coach (Cavallerio et al 2016). The extant research exploring the 5 environment of gymnastics has advanced our understanding of the role of culture in the 6 experience of current gymnasts.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This lack of open communication between athletes and coaches, together 1 with pain normalisation and impression management behaviours, was shown to influence the 2 development of overuse injuries. Overall, the gymnasts adhered to the cultural values and 3 norms inherent within the gymnastics environment by displaying appropriate behaviours 4 reinforced by the coach (Cavallerio et al 2016). The extant research exploring the 5 environment of gymnastics has advanced our understanding of the role of culture in the 6 experience of current gymnasts.…”
Section: Introductionmentioning
confidence: 94%
“…16 Findings from Cavallerio et al (2016) illuminated how young rhythmic gymnasts were 17 immersed in the cultural environment of an elite gymnastics club. Over time, the gymnasts 18 learned and accepted the values (e.g., importance of success, discipline) and norms (e.g., do 19 not skip training, do not talk back to the coach, be on time) that characterised their 20 environment, in the pursuit of being 'good gymnasts' (Cavallerio et al 2016). Indeed, rather 21 than disclosing their experiences of pain and injury to their coaches, the gymnasts in 22…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hill and Simons found coaches to be the more significant influence over youth decisions to specialize in a single sport (Hill & Simons, 1989). Youth players often learn a particular sports ethic from their coaches as well, one that often normalizes the experience of pain and the teaches youth to value "mental toughness" (Cavallerio, Wadey, & Wagstaff, 2016). Observational research of girls' softball teams found that coaches would frequently ignore players' complaints about pain, tell them to "shake it off," and even make jokes about those with physical complaints (Malcom, 2006).…”
Section: Coachesmentioning
confidence: 99%
“…Within this categorisation, the latter usually refers to pain that hurts and is rather difficult to endure, whereas the former is necessary or is believed to have a function in the body. Pain that is necessary can be the result of bodily work such as exercising and dancing, as the pain in this case is the proof to oneself that the body has been put under the necessary stress to progress, although how this pain is interpreted by the one in pain and by its immediate community is not necessarily the same, which blurs the lines between good and bad pain 18. Bendelow and Williams refer to good pain as the ‘constructive use of pain’, where pain is ‘an ally’3 rather than the enemy.…”
Section: Pain In the Literature: From Subjective To Intersubjective Mmentioning
confidence: 99%
“…However, as this article will illustrate as well, this dichotomy is constructed as a result of the overemphasis on chronic pain, and by overlooking the intersection between the two sensations. When the focus is shifted away from medically induced pain, the elusiveness of the lines between pain and pleasure can be seen even more clearly, as in the examples of physical exercise,18 sado-masochism21 and tattooing. Similarly, Amy Chandler addresses the elusiveness of the line between pain and pleasure by referring to self-injury and puts forth that ‘pleasure and pain became amorphous, fluid entities’ in her participants’ accounts 22.…”
Section: Pain In the Literature: From Subjective To Intersubjective Mmentioning
confidence: 99%